CCTV-Based Safety Monitoring in family Environments - Yulius Sutanto (Geviva Publisher, 2023)
The proliferation of Closed-Circuit Television (CCTV) systems has ushered in a new era of safety monitoring, extending its reach beyond public spaces into private family environments. This research paper delves into the emerging trend of CCTV-based safety monitoring within family settings. With the primary objective of enhancing household safety, this study investigates the implementation, effectiveness, ethical considerations, and potential implications of integrating CCTV technology into the domestic sphere. The paper begins by exploring the motivations behind adopting CCTV systems for family safety, addressing concerns such as child supervision, elder care, home security, and accident prevention. It examines the range of available CCTV technologies tailored for residential use, from basic monitoring setups to advanced features like real-time alerts, two-way communication, and facial recognition. A critical analysis of the effectiveness of CCTV-based safety monitoring in family environments is conducted, focusing on its impact on crime prevention, accident mitigation, and overall situational awareness. This analysis takes into account both quantitative data, such as crime statistics and accident rates, as well as qualitative data through surveys and interviews with households employing CCTV systems. Ethical considerations are a central theme of this research, as the intrusion into personal privacy is a significant concern when implementing surveillance technology within the family setting. The paper discusses the ethical implications of constant monitoring, potential breaches of trust, and the challenges of striking a balance between safety and individual autonomy. The legal frameworks surrounding CCTV use within homes are explored, highlighting the varying regulations across different jurisdictions. Furthermore, the study explores the psychological and social implications of introducing surveillance technology within the familial context. It examines the effects on family dynamics, communication patterns, and the mental well-being of household members, including children and teenagers. Ultimately, this research paper aims to provide a comprehensive overview of the growing trend of CCTV-based safety monitoring in family environments. By examining its benefits, challenges, and broader impacts, it contributes to the ongoing discourse on the integration of surveillance technology into private spaces. The findings of this study can guide policymakers, technology developers, and families in making informed decisions about the implementation of CCTV systems while upholding the values of safety, privacy, and familial harmony.